Critical Fusion Frequency and Audio-Visual Reaction Time as a Function of Age (International Journal of Physiology, 2019)
Background & objectiveAging is associated with physiological changes in functioning of different parts of the body. One of the changes commonly seen in elderly persons is slowness of the movements. Many studies concluded that audio-visual reaction time (RT) increases with age. Critical fusion frequency (CFF) is the frequency at which an intermittent light stimulus appears to be completely steady to the observer. It is been observed that CFF decreases with age. But whether this decrease is a progressive phenomenon is not clear. Hence, the present study was designed to investigate CFF in various age groups.Materials & methodThe study involved hundred subjects within the age group of 20–70 years. Subjects were divided into five age groups. Audio-visual reaction time and critical fusion frequency were measured. Data was statistically analyzed by using one way ANOVA for group wise changes in RT and CFF. Relationship between visual RT and CFF was found out by Pearson's coefficient of correlation.ResultsVisual RT and Audio RT were positively and significantly correlated with age whereas CFF was significantly and negatively correlated with age in male and females separately as well as when combined together. (p